ANALISIS IKLAN KENDARAAN MOBIL OLDSMOBIL, FORD, CHEVROLET, DAN ESSEX MOTORS DI KORAN BINTANG BORNEO TAHUN 1929 - Samuel, Rey; Norhidayat, Norhidayat; Wingkolatin, Wingkolatin (History Education Department, Universitas Mulawarman, 2023)
Car-type vehicles entered the Dutch East Indies in 1905 and expanded with advertising through local newspapers and one of them was the Bintang Borneo Newspaper. In the newspaper there are several car manufacturers who advertise their products, such as Essex Motors, Ford, Chevrolet and so on. This research discusses car advertising in the Bintang Borneo Newspaper. In general, this research aims to increase insight into the history, especially of car advertising in Indonesia, especially in the Bintang Borneo Newspaper in this research. In particular, this research aims to increase insight into the history of advertising by looking at the design language of various manufacturers who advertise their products in the Bintang Borneo Newspaper.